Otimismo e pessimismo em escolha sob incerteza - Paulo Roberto Santos Casaca (2010)
This paper provides an axiomatic foundation for preferences with uncertainty attitudes that the decision maker might be optimistic or pessimistic. Our main goal is to characterize preference relations like in Anscombe and Aumann (1963) represented by the functional, where fis an act, u is a von Neumann-Morgenstern utility over outcomes, C is a nonempty, convex and (weak*) compact subset of probabilities measures, and A is a referential event that identifies the separation between optimistic and pessimistic attitudes towards ambiguity. In addition to the usual assumptions on the preference relation as transitivity, completeness, non-degeneracy, continuity, monotonicity and certainty independence, we assume one key condition namely event-dependence, that insure the existence of a neutral event A in which the decision maker is pessimistic about bets in favor of sub-events of A and optimistic about bets against A. This preference generalizes the well known Maxmin Expected Utility Theory proposed by Gilboa and Schmeidler (1989), and provides a novel model capturing both uncertainty averse and uncertainty seeking attitudes.